An Appraisal of Factors Influencing Adoption of Agricultural Innovations: Insights from Selected Developing Countries - Rachel Moyo; Abiodun Salawu (Journal of International Agricultural and Extension Education, 2017)
Research has revealed that different factors influence adoption of agricultural innovations by farmers. These factors include characteristics of innovations comprising relative advantage, complexity, compatibility, trialability and observability as discovered by Rogers (1983), and technology characteristics, information sources, knowledge, awareness, attitude, and group influence (Odalele, 2005, p. 250). The diffusion model was considered the main theoretical model for agricultural extension and the development of agricultural advisory services (Padel, 2001, p. 40). The diffusion process influences the success or failure of agricultural development programmes. Factors influencing adoption of agricultural innovations were appraised by reviewing selected empirical studies. This could influence agricultural communication agents to consider the interaction of factors in the diffusion and adoption process in designing their communication strategies in the light of improving adoption.